Understanding the psychosocial impact of cancer in adolescence and young adulthood: a mixed-methods assessment of the perspectives of patients, survivors, and healthcare professionals - Kandler, Liane S. (My University, 2019)
The goal was to assess the perceived ability of healthcare professionals to discuss adolescent and young adult oncology (AYAO) specific issues, and the use of a documentary film as awareness and teaching tool. Healthcare professionals and students (n = 81) were recruited during training sessions at three Canadian cancer centres and invited to complete a brief questionnaire before and after viewing a documentary film depicting an outdoor expedition for AYA cancer patients. Demographics, work experience, and self-perceived AYAO knowledge was assessed pre-film. Understanding of AYAO needs, emotions, and life issues was queried using a 5-pt ordinal scale and using open-ended questions both pre- and post-film. Post-film, respondents were asked to reflect on whether they had learned anything new (yes/no). Medical staff and students reported a statistically significant increase in understanding of AYAO emotions, needs, and life issues from pre- to post-film, with 96% of the sample reporting they learned something new from viewing the film. Qualitative data support an increased post-film recognition of isolation as a key emotion and decreased emphasis on the treatment-related concerns as key life issues. Notably, the need for support was well recognized both pre- and post-film. This research provides preliminary support for the use of film as a teaching tool. Further research is warranted to explore short and long-term benefits from the patient and professional standpoint.
Keywords: Cancer in adolescence and young adults; Psychosocial care (adolescent/young adult)